Numerical Analysis for Streamer Discharge at the Discharge Transition from the Second to the Third Mode in Transformers Oil - Khalaf , Sami A.; Khalaf, Thamir H. (Iraqi Journal of Science, 2024)
This study is a numerical analysis of the transition process from the second to the third mode in transformer oil. In this study, it was determined how to change from the second to the third mode, which is thought to be a precursor to the process of electrical breakdown, which results in a significant loss of electrical energy and harm to electrical devices and equipment. The initiation time, length, rate of propagation velocity, and radius of the streamer discharge were determined. The transition from the second to the third mode during the electrical discharge process may lead to the occurrence of an electrical breakdown, which is one of the greatest challenges facing scientists and engineers who deal with the electrical power of transmission and generation devices. The model was designed by AutoCAD software, which included two electrodes: a needle, with a tip radius of (4µm), and a plate, with a gap of (1 mm) between them. The gap between the two electrodes was filled with transformer oil. The equations, which are Poisson’s equation and the continuity equations for positive and negative ions and electrons, which are generated by applying an applied voltage (from 27 kV to within 278 kV), had been solved by a simulation process. All the schematics and drawings were extracted by the Comsol Multiphysics program.